PERAN PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER BANGSA YANG BERMORAL - Fadilah Sari, Fadilah; Br Ginting, Nursamsiah (Proceeding International Seminar of Islamic Studies, 2024)
Islamic Religious Education has long been an integral part of shaping the moral character of societies in various countries. Its primary aim is to cultivate morality, ethical values, and behaviors in accordance with the teachings of Islam. This article discusses the significant role of Islamic Religious Education in shaping a morally upright national character. Within this context, emphasis is placed on Islamic values contributing to the formation of a moral character, effective educational strategies integrating these values into the curriculum, and the positive impact of implementing Islamic Religious Education on the nation's moral and ethical development. This research utilizes descriptive analysis methods to provide a comprehensive overview of how Islamic religious education serves as a fundamental pillar in shaping the moral character of the nation.